An examination of works for wind band: Yorkshire ballad by James Barnes, La vigen de la macarena arranged by Charles Koff, Provenance by Robert W. Smith, Nessum dorma arranged by George Hattendorf, and Brighton beach march by William Latham - Bradford, Matthew S. (Kansas State University, 2007)
The following document is research and analysis from the comprehensive examination question based on the Graduate Conducting Recital of Matthew S. Bradford. The recital, performed by the Clay Center Community High School Band, was given in the Martyn/Snodgrass Auditorium of Clay Center Community High School on Monday, January 29, 2007 at 7:30 PM. The repertoire included Yorkshire Ballad by James Barnes, La Virgen De La Macarena arranged by Charles Koff, Provenance by Robert W. Smith, Nessum Dorma arranged by George Hattendorf, and Brighton Beach March by William Latham. This document contains theoretical and historical analysis, and outlines the procedures of planning and performing the graduate conducting recital.
Keywords: Music; Conducting; analysis; Education, Music (0522); Music (0413)